Nuevo Dique de Poniente del Puerto de Almería (1.a fase). Issue 2 (1st July 2016) - Capote, A.; Bayo, A.; Andújar, C.; González, J.M.; Zamora, D.; Corral, J.
Abstract: This paper goes through the main three stages, planning, design and construction, of a singular port infrastructure: the new western breakwater of Almería port. The main issues of each of these phases are outlined along this document, aiming to present the complete cycle of this protection infrastructure, from its conception and design to its materialization. The article is mainly focused on the design stage, since this case is special for having been developed by means of level I and level III Methods. Level III methods are a relatively novelty both in the national and international scenario, since they use probabilistic methods for the design. This article could be considered as a guide for the design of future breakwaters, as it includes the standard methodology for level I methods as well as the procedure for verifications by means of level III methods.